Banks in equity market - a risk analysis - K S, Nemavathi; A, Ashraf Ali (Journal of Management and Science, 2012)
Equity market is often considered as the main engine driving the economy. In emerging countries, equity market plays a vital role in economic development. Many emerging markets, firms would need large quantum of fund to expand and be able to pursue the prevalent high growth rates. Equity market is the only liquid financial market in many emerging countries and hence its role in economic development cannot be overemphasized.In addition, all over the world, financial markets are getting less insular. The investors in developed countries are seeking investment opportunities beyond the confines of their domestic economy to enhance return and diversify risks. The investment in stock involves many risks. The investors have to carry analysis before investing in any stocks. Most of the investors are unaware about the analysis to be carried out before investing. This study involves analysis of earnings per share, price to earnings and analysis of risk through beta value, of the banks in equity market. Technical analysis helps the investor to know whether the stock is in over sold region or over bought region and to find any trend reversals. Based on these analysis investor can make buy or sell decision. The researcher concludes that the maximum return is based on the maximum risk in which the investor is going to face.